Bürgerliche Mitgliedschaft in Religionsgemeinschaften Studie über die Rechtsbeziehungen der Mitglieder zu den römisch-katholischen, evangelischen, jüdischen und islamischen Religionsgemeinschaften in Deutschland - Kuntze, Johannes (Universitätsverlag Göttingen, 2013)
This doctoral thesis treats the membership law of churches and religious communities. It discusses the questions of which framework is given by national law, in which cases the rights of religious communities diverges from that law and if membership must strictly be voluntary. Following a historical as well as legal classification, this thesis considers the legal relationship of members with Christian, Jewish and Islamic communities in Germany.